Prevalence of Eating Behaviors and Their Influence on Metabolic Control of Children With Type 1 Diabetes Mellitus - Samaneh Farnia; Arian Jahandideh; Daniel Zamanfar; Mahmood Moosazadeh; Akbar Hedayatizadeh-Omran (Mazandaran University of Medical Sciences, 2023)
Background: Since a comprehensive study of eating disorders in children with type 1 diabetes in the Iranian population is necessary, this study aimed to investigate the prevalence of eating behaviors and metabolic control status of children and adolescents with diabetes mellitus. Objectives: The present cross-sectional study aim to explore the prevalence of eating behaviors and their influence on metabolic control of children with type 1 diabetes mellitus. Methods: In this cross-sectional study, all children and adolescents 6 to 12 years old with diabetes were included. First, the prevalence of eating-related behaviors in participants was assessed and recorded. Then the recorded data were statistically analyzed. Results: The Mean±SD age of the study participants was 8.92±1.925 years. One hundred children with food approach scores above 12.29 had food-approach behaviors, and 78 children with food avoidance scores above 11.85 were classified as having food avoidance behaviors. The relationships between food-approach behaviors and hemoglobin A1C (HbA1c) and insulin dose, body mass index (BMI), and lipid profile were significant (P<0.05). Nevertheless, the relationship between these variables and food avoidance behaviors was not significant (P>0.05). Conclusions: High BMI, high insulin dose, increased lipid levels, and high HbA1c are associated with an increased eating tendency in children. Therefore, these children should be evaluated for disordered eating behaviors.